Keep sharp [compact disc, unabridged] : how to build a better brain at any age - Gupta, Sanjay, 1969- (Simon & Schuster Audio, 2020)
Dr. Sanjay Gupta offers insights from top scientists all over the world, whose cutting-edge research can help heighten and protect brain function and maintain cognitive health at any age. He debunks common myths about aging and cognitive decline, explores whether there's a 'best' diet or exercise regimen for the brain, and explains whether it's healthier to play video games that test memory and processing speed or to engage in more social interaction. Discover what we can learn from 'super-brained' people who are in their 80s and 90s with no signs of slowing down and whether there are truly any benefits to drugs, supplements, and vitamins. Dr. Gupta also addresses brain disease, particularly Alzheimer's, answers questions about the signs and symptoms, and shows how to ward against it and stay healthy while caring for a partner in cognitive decline. He likewise provides a personalized twelve-week program featuring practical strategies to strengthen the brain every day.